Comparison of The Frequency of Necrotizing Enterocolitis with or Without Probiotics Use in Preterm Neonates - Khan, Erum Saleem; Asad Ur Rehman; Naseem, Shabnam; Wahab, Fakhra (Indus Journal of Bioscience Research, 2025)
Background: Necrotizing enterocolitis (NEC) is a gastrointestinal tract medical emergency among premature neonates, notoriously inducing severe morbidity as well as death. Preventive strategies have a central role, particularly in low-income nations. Despite potential with using probiotics in reducing NEC frequency, benefit in selective groups and settings is under researched. Objective: To compare the frequency of necrotizing enterocolitis with or without probiotics use in preterm neonates. Study Design: Randomized controlled trial. Duration and Place of Study: The study was conducted from August 2024 to January 2025 at the Department of Obstetrics and Gynecology, CMH Rawalakot. Methodology: A total of 128 preterm neonates (